Demolition in regeneration megaprojects: The case of Wien Hauptbahnhof - Kosmowski, Piotr. Autor (IGiPZ PAN, 2019)
Regeneration of centrally located city areas has been increasingly more often undertaken as a regeneration megaproject exercise. In European cities there are vast post-railway areas, which, if transformed, can produce morphological and functional changes. Against this background, investigating demolition as part of transformation of the existing spatial and functional structures is an interesting option. Transformations proposed for the downtown area of Vienna previously occupied by the Wien Südbahnhof railway station include the reconstruction of 109 ha formerly used exclusively by railway sector operators. The research problem boils down to the question: what was the course of demolition of the area covered by modernisation works carried out as a megaproject and how has it transformed space organisation on the spot? The paper analyses the sequence of urban renewal initiated in Vienna in the area adjacent to the new Wien Hauptbahnhof railway station and identifies the outcomes of the process. Regeneration project triggered the decision to completely demolish all elements of the existing railway infrastructure and to reconstruct it anew on a much smaller area. Recuperated post-railway land was made available to housing developers, as well as to service facilities and leisure projects, which expand central area of the city.
24 cm
Keywords: megaproject; demolition; regeneration; railway areas; Wien Hauptbahnhof; Wien Südbahnhof